Treatment of Distal Anterior Cerebral Artery Aneurysms with Flow-Diverter Stents: A Single-Center Experience - Cagnazzo, F.; Cappucci, M.; Dargazanli, C.; Lefevre, P.-H.; Gascou, G.; Riquelme, C.; Bonafe, A.; Costalat, V. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Flow diversion for aneurysms beyond the circle of Willis is still debated. Our aim was to evaluate the safety and efficacy of flow diversion treatment of distal anterior cerebral artery aneurysms.MATERIALS AND METHODS: Consecutive patients with distal anterior cerebral artery aneurysms treated from January 2014 to October 2017 were evaluated retrospectively with prospectively maintained data. Treatment was performed only for unruptured or recanalized aneurysms after coiling. Technical feasibility, procedural complications, aneurysm occlusion (O'Kelly-Marotta grading scale), and clinical outcome were evaluated.RESULTS: Fifteen patients were included in the study, with 17 distal anterior cerebral artery saccular aneurysms treated with flow-diverter stents. Mean aneurysm size was 4.25 ± 3.9 mm; range, 2–9 mm. Flow diversion was used as retreatment among 6 previously coiled aneurysms (5 ruptured and coiled in the acute phase, and 1 unruptured and recanalized). Stent deployment was technically successful in all cases. During the perioperative period, 1 patient experienced a transient minor stroke (6%), whereas 2 patients reported acute in-stent thrombosis with disabling ischemic complications (13%). Fourteen patients and 16 aneurysms were available during a mean radiologic follow-up of 12 months (range, 3–24 months). Overall, 12 (75%) aneurysms were completely occluded (O'Kelly-Marotta grading scale score D), 1 aneurysm (6%) showed near-complete occlusion (O'Kelly-Marotta grading scale score C), and 3 aneurysms (19%) were incompletely occluded (O'Kelly-Marotta grading scale, score B). All 6 aneurysms previously coiled were completely occluded after flow diversion, whereas 70% of aneurysms treated with flow diverters alone showed complete/near-complete occlusion (O'Kelly-Marotta grading scale C–D). There were no cases of aneurysm rupture, in-stent occlusion, or retreatment during long-term follow-up.CONCLUSIONS: Treatment of distal anterior cerebral artery aneurysms with flow-diverter stents is feasible and effective, with high rates of aneurysm occlusion. Flow diversion plus coiling, in the retreatment of lesions previously coiled, allowed higher rates of occlusion compared with flow diverters alone. However, the risk of ischemic complications is not negligible, and flow-diversion treatment should be evaluated only for aneurysms not amenable to simple coil embolization.ACAanterior cerebral arteryOKMO'Kelly-Marotta grading scale